1978
DOI: 10.1002/jbm.820120307
|View full text |Cite
|
Sign up to set email alerts
|

Compliance as a factor effecting the patency of a copolyurethane vascular graft

Abstract: A new solid-wall vascular graft which has a compliance approximating that of the natural artery has been prepared from a copolyether-urethane material. Six of nine of these compliant grafts implanted in dogs were patent on removal, the longest implant time being 77 days for a 4-mm I.D. femoral artery graft. This is in contrast to noncompliant grafts of the same copolyurethane in which failure usually occurred within 48 hr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(31 citation statements)
references
References 3 publications
1
30
0
Order By: Relevance
“…[11][12][13][14][15] For example, compliance mismatch between a vascular graft and the native vessel into which it is implanted has been demonstrated to be a critical factor, leading at times to the formation of neointimal hyperplasia and stenosis. 16,17 The biomechanical properties of a TEVG are determined primarily by the sum of the mechanical properties of the scaffold and the biomechanical properties of the ECM. In the case of a biodegradable scaffold, this process is dynamic and changes as the scaffold degrades and neotissue forms.…”
mentioning
confidence: 99%
“…[11][12][13][14][15] For example, compliance mismatch between a vascular graft and the native vessel into which it is implanted has been demonstrated to be a critical factor, leading at times to the formation of neointimal hyperplasia and stenosis. 16,17 The biomechanical properties of a TEVG are determined primarily by the sum of the mechanical properties of the scaffold and the biomechanical properties of the ECM. In the case of a biodegradable scaffold, this process is dynamic and changes as the scaffold degrades and neotissue forms.…”
mentioning
confidence: 99%
“…10 Most polymeric vascular prostheses have a material compliance greatly exceeding that of the natural vessel. Lyman et al 11,12 reported that a mismatch in material compliance between the polymer and the vessel initiates thrombosis and stimulates initial intimal hypertrophy. For many diseases of the sclera, such as pathologic myopia, the compliance of the diseased sclera is much higher than that of normal sclera.…”
Section: Discussionmentioning
confidence: 99%
“…Molded specimens (2 Â 10 Â 20 mm 3 ) were cut in the half with a knife (to avoid edge effects), provided with a seam of surgical suture (PP monofilament, suture size 6-0-0.07 mm in diameter) by the aid of a special gauge (seam distance 4 mm from the edge), clasped into a modified tensile testing arrangement (Figure 3 left) and loaded with a speed of 1 mm/min. A typical curve of the tear resistance test is shown in Figure 3 right.…”
Section: Suture Tear Resistance Testsmentioning
confidence: 99%
“…[3] Therefore, we are interested in the development of suitable blood vessel substitutes out of biocompatible, mechanically tailorable photopolymers. We designed our resin formulation to be suitable for rapid prototyping which offers us the high range of shaping possibilities of additive manufacturing (AM).…”
Section: Introductionmentioning
confidence: 99%